Applying Environmental-STEM Approach on Pollution Issue Material to Enhance Students’ Problem-Solving Skills - Wiwit Artika; Cut Putri Amalya; Safrida Safrida; Maulida Maulida; Afandi Afandi; Lina Ratna (Jurnal Penelitian Pendidikan IPA, 2023)
The learning process has not emphasized developing problem-solving skills since students memorize concepts, thus, the skills are not optimally trained. This study aimed to compare students' problem-solving skills between groups of students using the Problem-based Learning (PBL) model with the E-STEM-based student worksheet and the PBL-only model on environmental pollution at one of the Islamic Senior High Schools in Banda Aceh, Indonesia. This study employed a quantitative method with an experimental research approach using the pretest-posttest control group design. The population was all grade 10 students at the school studied, and the sample was 84 students using a total sampling technique. The instrument was ten long answer questions to measure problem-solving skills. Analysis of students' problem-solving skills data was done by t-test at a significant level of 0.05. The results indicated differences in students' problem-solving skills after experiencing the PBL model applied combined with an E-STEM-based student worksheet on environmental pollution.